Literature Review on Psychosis in Sub-Saharan Africa - Otu, Mkpoikanke Sunday (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2024)
Abstract: The scoping review explores the prevalence, diagnosis, and treatment of psychosis in Sub-Saharan Africa, highlighting the unique cultural and systemic challenges faced in the region. Despite an estimated global psychosis prevalence of 3%, Sub-Saharan Africa experiences a disproportionate burden, exacerbated by poverty, under-resourced healthcare systems, and cultural stigmas. Studies report a varying prevalence of psychotic symptoms across different countries, such as Kenya (8%) and Tanzania (3.9%). However, due to minimal mental health resources, psychosis often remains undiagnosed or untreated, particularly in rural areas. The review emphasizes the cultural lens through which psychosis is viewed, with many communities attributing symptoms to witchcraft, spiritual possession, or divine punishment. Consequently, individuals frequently seek care from traditional healers before accessing formal psychiatric services. The stigma surrounding mental illness further deters timely medical intervention, often leading to prolonged untreated psychosis and poor health outcomes. Diagnosis of psychosis in Sub-Saharan Africa faces additional barriers due to the reliance on Western diagnostic tools, such as the DSM-5 and ICD-10, which may not align with local cultural norms. Behaviors considered psychotic in Western contexts might be interpreted as spiritual experiences in African settings. As such, the absence of culturally adapted diagnostic instruments complicates accurate diagnosis and treatment. The treatment landscape is similarly complex, with limited access to psychotropic medications and mental health professionals. The scarcity of community-based mental health services results in long treatment delays and high relapse rates. The review calls for developing culturally appropriate diagnostic tools, expanding mental health services, and addressing stigma to improve psychosis care in Sub-Saharan Africa. Addressing these issues is essential to reducing the burden of untreated mental illness and enhancing mental health outcomes in the region. Keywords: Psychosis; Sub-Saharan Africa; mental health; diagnosis; Treatment.